Effectiveness of herbal toothpaste with Ambon Banana tree sap extract (Musa paradisiaca var. sapientum) on inhibiting the growth of streptococcus mutans serotype-d (omz-176) bacteria - Akhsanitaqwim, Yochidamai; Wirasat, Galang; Nugraha, Fahim Rafa (Public Health Risk Assesment Journal, 2025)
Background: This study aims to determine the antibacterial activity of Ambon banana stem sap extract against Streptococcus mutans serotype-d (OMZ-176) and to evaluate the physicochemical characteristics of toothpaste formulated with Ambon banana stem sap extract, along with its antibacterial activity against S. mutans serotype-d (OMZ-176). Methods: This study involved the extraction of Ambon banana stem sap, its phytochemical and antibacterial testing, and the formulation of herbal toothpaste. Quality tests included homogeneity, viscosity, pH, foaming, and spreadability. Data were analyzed using descriptive analysis and ANOVA to assess effectiveness and product quality. Findings: The research employed an experimental method on a laboratory scale. Ambon banana stem sap extract inhibited the growth of S. mutans at concentrations of 600 mg/mL and 700 mg/mL, with inhibition zone diameters of 9.405 ± 0.0613 mm and 10.623 ± 0.0044 mm, respectively. Toothpaste containing Ambon banana stem sap extract at a concentration of 600 mg/mL exhibited characteristics of a creamy color, thick consistency, homogeneity, a pH of 9.4, foam height of 0.8 cm, viscosity of 196.58 dPa·s, and a spreadability of 3.65 cm. Meanwhile, toothpaste with a 700 mg/mL extract concentration had a brownish color, thick consistency, homogeneity, a pH of 9.43, foam height of 0.5 cm, viscosity of 196.65 dPa·s, and a spreadability of 3.38 cm. Both toothpaste formulations at 600 mg/mL and 700 mg/mL were effective in inhibiting the growth of S. mutans, with inhibition zone diameters of 13.6233 ± 0.8519 mm and 11.565 ± 0.8674 mm, respectively, categorized as strong inhibition. Novelty/Originality of this Study:This study presents an innovative approach to oral health by using Ambon banana stem sap as a fluoride alternative, showing strong antibacterial properties and offering a safer, natural option for effective oral care.